Development of STEM-PjBL-based e-modules to build the nature of science on the topic of object properties and changes in the state of matter - Zahra, Amelia; Rohman, Fatkhur; Adha, Mohammad Mona; Nurwahidin, Muhammad (Indonesian Journal of Science and Mathematics Education, 2025)
This study aims to describe the development of a STEM-PjBL-based e-module (electronic module) designed to improve students' understanding of the nature of science (NoS) in the topics of the properties of objects and changes in the form of objects. The urgency of this study lies in the limited availability of interactive digital teaching materials that use real-life science concepts. The STEM-PjBL-based e-module was developed using the Plomp Model, which consists of three stages: initial investigation, design and development, and evaluation. The research results indicate that this e-module is highly valid (86.12%), highly practical (96.68% according to teachers and 95.06% according to students), and highly effective with an N-gain score of 0.72. The findings suggest that STEM-PjBL-based e-modules can significantly build learners' NoS and support innovative technology-integrated learning in primary schools. These results imply that integrating STEM-PjBL in digital modules offers a promising approach to enhance scientific understanding while enriching teaching practices with relevant, student-centred, contextualized content.